Distribution of Candida species among HIV-positive patients with oropharyngeal candidiasis in Accra, Ghana - Kwamin, Francis; Nartey, Nii Otu; Codjoe, Francis S; Newman, Mercy J (The Journal of Infection in Developing Countries, 2013)
Introduction: Oropharyngeal candidiasis is a common occurrence in the course of human immunodeficiency virus (HIV) disease progression. Changes in the clinical severity of oropharyngeal candidiasis and type of Candida species profile may be a reflection of immunological changes in patients. The aim of this study was to undertake a baseline Candida species identification for future reference. Methodology: Oral swabs of 267 HIV-infected patients with oropharyngeal candidiasis were cultured and Candida species were identified by API 32 C. Results: A total of 201 (75.3%) Candida species and 10 (3.7%) non candida fungi were identified. Twenty different Candida species were isolated. Candida albicans was the most prevalent species (68.5%) followed by C. tropicalis (7.4%), C. krusei (6.4%), C. parapsilosis (3.0%) and C. sake (2.5%). Other species ranged from 0.5% to 1.5%. Positive culture was independent of whether patients were on anti-retroviral therapy or not. Conclusion: Of all Candida isolates, 68.5% were identified as C. albicans. Since other uncommon species were also isolated, it may be necessary in this group of patients to identify Candida species causing severe infections.